Reading aloud as Interface between Written and Oral Literatures in Britain, Ireland and Kenya - Kaboré, Andre (Advances in Social Sciences Research Journal, 2016)
Literary criticism, especially in Europe, has not sufficiently shown and acknowledged the reciprocal interaction between oral and written traditions. Though it is easy to believe, with the theory of new historicism, that early written literature took over material from oral literature, the passage from print literature to the oral tradition rarely comes to consideration. The objective of this paper is, using the theory of orature, to show, with the examples of the works by Charles Dickens, William Carleton and Ngugi Wa Thiong’o that went from written literature to oral literature, that reading aloud serves as a process in went back to oral literature through. It is hoped that the realisation of the oral appropriation of printed literature in this process will change our approach to it and lead us to develop it as an alternative form of literary acquisition that is more efficient in some contexts.